(untitled) (Research, Society and Development, 2021)
Objective: To evaluate virtual and augmented technology treatments in the management of phantom limb pain. Methodology: The search for scientific literature was carried out in the databases Pubmed, Scielo, Lilacs, Web of Science, Scopus and CINAHL, of primary studies published in the period from 2015 to 2020, with individuals diagnosed with phantom limb pain. 380 articles were identified, which after the eligibility criteria resulted in 16 studies. Results: Studies with the referred realities showed a decrease in the intensity and perception of pain in the limb, based on the pain questionnaire and the researches associated with the augmented reality, the individuals improved in their daily activities as well as in the quality of sleep. Conclusion: Virtual and augmented reality presents itself as an efficient treatment strategy, however, studies with samples and more time are needed to verify long-term efficiency.